2015
DOI: 10.1007/s10934-015-9913-0
|View full text |Cite
|
Sign up to set email alerts
|

Controlled release of Diclofenac, an anti-inflammatory drug by nanocompositing with layered zinc hydroxide

Abstract: The anti-inflammatory drug, Diclofenac (DIC) anion, was intercalated into the layered zinc hydroxide (LZH) by ion-exchange method. Then, the DIC-LZH/ Chitosan nanocomposite was prepared by coating of Chitosan on DIC-LZH. LZH intercalated with DIC was successfully encapsulated into Chitosan by precipitation method. The structures of the obtained products were studied by powder X-ray diffraction, FT-IR spectroscopy, scanning electron microscopy, and thermal analysis. The XRD patterns and FTIR analyses showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…ZnO exhibits a distinctive pattern with five sharp reflections at 2 = 30-60 ∘ region, corresponding to 100, 002, 101, 102, and 110 lattice planes which indicate high crystallinity of the precursor. Previous studies of ZLH intercalated with nitrate ions show sharp diffraction peak with basal spacing of 9.6-9.9Å recorded around 2 = 9.3 due to the 200 planes of the monoclinic structure [24,25]. The basal reflections of VAN are shifted to lower 2 with -spacings of 19.8Å, 9.9Å, and 6.6Å.…”
Section: Controlled Release Studymentioning
confidence: 81%
“…ZnO exhibits a distinctive pattern with five sharp reflections at 2 = 30-60 ∘ region, corresponding to 100, 002, 101, 102, and 110 lattice planes which indicate high crystallinity of the precursor. Previous studies of ZLH intercalated with nitrate ions show sharp diffraction peak with basal spacing of 9.6-9.9Å recorded around 2 = 9.3 due to the 200 planes of the monoclinic structure [24,25]. The basal reflections of VAN are shifted to lower 2 with -spacings of 19.8Å, 9.9Å, and 6.6Å.…”
Section: Controlled Release Studymentioning
confidence: 81%
“…If it is tempting to try a direct correlation between the density of surfactant and DFC adsorbed amounts, this could not be done here since the adsorption depends on the BDTA organization and the diversity of the driving adsorption forces as the results of Na-Mt display and BDTA0.4-Mt.Indeed, in the latter case, the BDTA0.4-Mt organoclay shows a reasonable increase of its interlayer space while almost 50% of its whole surface displays a lipophilic behavior that may restrict the possibility of adsorption of DCF and thus explains a linear lineshape for the adsorption. In contrast, the improvement of the DFC removal is meaningful for BDTA density > 1CEC with a adsorption capacity greater than 260 and about 380 % for BDTA-Mt and BDTA4-Mt respectively compared to those of both BDTA0.4-Mt and Na-Mt.By comparing the maximum amounts at the plateau to the theoretical ones that can be adsorbed onto the layered materials showing a specific surface area of 750 m² g -1 and a mean molecular radius of 3 Å for DFC29,30 , the experimental adsorbed values represent about 20%, 52%, et 76% of the whole accessible surface, exceeding that of the external surface (with the hypothesis of a monolayer adsorption). If the adsorption of DFC leads to a shift of the 00l reflection to low angular value (Figure SI-4), attesting a possible intercalation within the interlayer space; the diffractogramms of the whole organoclays after being in contact with diclofenac do not show any structural changes (i.e.…”
mentioning
confidence: 99%
“…These images exhibited that the transformation of LZH into an IBU-LZH nanohybrid produced surface morphology transformation and the particle size of IBU-LZH nanohybrid was reduced in comparison with the layered hydroxide. 16 This indicated that the IBU anions intercalated into the interlayer space of LZH. Figure 6c shows a non-uniform structure for IBU-LZH/chitosan.…”
Section: Surface Morphology Studymentioning
confidence: 98%
“…10-12 * Author for correspondence (ha.nabipour@gmail.com) LZHs are currently being used as an additive for slow release herbicides and drugs. [13][14][15] Some drugs have been intercalated into LZH, including diclofenac sodium, 16 amoxicillin trihydrate, 17 ciprofloxacin 18 and cetirizine. 19 There are many approaches that can be used to synthesize the LZH nanohybrid such as the co-precipitation method, 20 thermal decomposition method 21 and ion-exchange method.…”
Section: Introductionmentioning
confidence: 99%